Use of metabolic engineered Escherichia coli strains for enhanced biohydrogen production from palm oil mill effluent - Taifor, Azam Fikri (2017)
Biological hydrogen production offers a method through which biomass can be utilized for production of premium-energy carrier as an alternative energy for replacement of non-renewable fossil fuels. The present work aims to elucidate the substrate utilization in biohydrogen production from palm oil mill effluent (POME) by E. coli strains. The experiments were performed in 150 mL serum bottles and the cultures were supplemented with autoclaved-pretreated POME to investigate the potential use of various carbon sources and its preference towards biohydrogen production. The cultures conditions were maintained at 37 C for 24 h with mild agitation at 120 rpm. The maximum hydrogen yield (MHY) of 0.68 mol H2 / mol total sugars with 81% substrate consumption based on total sugar and hydrogen productivity of 3552 mol / 1010 cfu were obtained from engineered E. coli BW25113 after 24 h of fermentation. The biohydrogen production by modified strain was enhanced by 3.5 fold compared to wild type strain. On the other hand, studies on the utilization of various substrates on the synthetic medium showed that the highest MHY of 0.77 mol H2 / mol total sugar was obtained from fermentation of fructose by engineered E. coli BW25113. The preference of the substrates based on the synthetic medium for biohydrogen production was in the following order; fructose > glucose > formic acid. These findings indicated that the use of modified strain E. coli BW25113 has enhanced biohydrogen production from POME.